ANALISIS PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) MEDAN TERHADAP KINERJA PEMERINTAH KOTA MEDAN - Parlindungan Marpaung; Julisman Zai (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UDA, 2020)
ABSTRACT Based on Law No. 9 of 2015 concerning Regional Government, The Regional people's representative assembly (DPRD) has a legislative function, a supervisory function, and a budget function. Thus, this study aims at finding out the DPRD's supervision of the performance of the Medan city government and to find out what are hampering the DPRD's supervision of the performance of the Medan city government. This study uses a qualitative method. The sampling technique uses purposive sampling technique. Data was mining carried out from observation, in-depth interviews with the Medan City DPRD and its staff and documentation from the field. The location of the study was conducted in the secretariat of the Medan City DPRD with its address at Jl. Captain Maulana Lubis No. 1 Petisah. Tengah. The results of the study illustrate that the supervision activities referred to can be seen in the work program and elaboration of the work plan of the Medan City DPRD. The supervisory activities are arranged in the form of hearings, working visits, the formation and supervision of government performance. Obstacles in conducting supervision are those that originate from the internal board and from outside the board. Internal barriers such as education problems. Obstacles from outside the Council are changes in legislation regarding regional government and lack of community participation and media on the implementation of local government performance.